Pengaruh Kesadaran Halal, Sertifikasi Halal dan Influencer Marketing Terhadap Minat Beli Konsumen yang Berdampak pada Kepercayaan Konsumen pada Event Mambo Kuliner Tasikmalaya - Windi Yuliani; Neneng Nurhasanah; Ramdan Fawzi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The city of Tasikmalaya has started pushing for halal certification since 2019. LP3H said that there are still many who are indifferent to halal certification and do not understand the urgency of halal in terms of literacy and education. Apart from that, MSMEs in Tasikmalaya City use influencer marketing services to promote their products, but some marketing influencers do not pay attention to which MSMEs are halal certified or not. Data collection techniques using questionnaires with a sample of 200 people. The research results showed that halal awareness, halal certification, influencer marketing, purchasing interest and consumer trust had an average score of 83% to 92% and were in the 'Very Good' category. Partial Halal Awareness does not have a significant effect on consumer buying interest, while Partial Halal Certification and Influencer Marketing have a significant effect on Buying Interest. Halal Awareness, Halal Certification, Influencer Marketing Simultaneously influence Consumer Purchase Interest at the Tasikmalaya City.